Temperature stress alters transcriptomic and physiological responses in hybrid grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) - Matusin, Saleema; Mujar, Ellia Kartini; Christianus, Annie; Ariffin, Norazrin; Salleh, Annas; Low, Chen Fei; Chong, Chou Min; Md Yasin, Ina Salwany; Abu Bakar, Muhammad Hafiz; Esa, Yuzine; Kua, Beng Chu (KeAi Communications, 2025)
The continuous intensification of climate change exposes hybrid grouper to fluctuating temperatures, affecting physiology, immunity, and overall performance. This study investigates the molecular, biochemical, and histological responses of hybrid grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) exposed to one day (21–33 °C) and five days (22–31 °C) temperature fluctuations. Sub-adult fish (20.95 ± 0.64 cm) were grouped into acute (A), tolerant (R), and sensitive (S) categories based on behavioural responses such as feeding and swimming behaviours. Skin transcriptome profiling revealed that the DEGs were most significantly enriched in genetic information processing networks, including pathways involved in folding, sorting and degradation, translation, and transcription. Genes involved in protein processing in the endoplasmic reticulum (skp1, ero1a, rpn2) were significantly upregulated in A vs C and R vs C groups, while genes involved in energy metabolism were significantly upregulated in S vs C group. However, genes involved in the ribosome pathway (rpl22, rps15, rpl9, rps21, rpl12, rpl19) were significantly downregulated across all three comparison groups. Biochemical markers, including elevated alanine aminotransferase (ALT) and glucose (GLU) levels and reduced lactate dehydrogenase (LDH) activity indicate metabolic disturbances. Histopathological alterations included hepatocytic vacuolation, inflammatory infiltration in the liver, and melanomacrophage aggregation in the spleen and head kidney, indicating systemic stress and immune activation. This integrated analysis reveals significant molecular and physiological mechanisms underlying thermal stress responses in hybrid grouper. The identified genes, pathways, and biomarkers offer valuable insights for improving stress resilience and guiding management strategies in aquaculture under climate change.